Pengaruh Harga, Kualitas Pelayanan, Promosi Dan Kualitas Produk Terhadap Loyalitas Konsumen Pada Indogrosir Malang - Puspita Rahma Tristanti; Siti Asiyah; Afi Rahmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThis study aims to determine and analyze the effect of price, service quality, promotion and product quality on consumer loyalty at indogrosir Malang. This research is a type of explanatory research, with a quantitative approach. The analytical method used is multiple linear regression analysis. The sample used in this study using the Maholtra formula with purposive sampling technique obtained 115 respondents.The results of this study indicate that partially there is a significant influence between Price, Service Quality, Promotion and product quality, has a significant effect on customer loyalty at Indogrosir Malang. Keywords: Price, Service Quality, Promotion, Product Quality and Consumer Loyalty